Locomotor Disability Dexterity Interface - Abhishek Kumar Saw, Aayush Mishra, Kashika Parmar, Saurabh Kansara (Mathematical Statistician and Engineering Applications, 2023)
Disability is a public health issue which is defined as the limitation or inability to accomplish a task or activity within the parameters thought to be typical for humans, in locomotive disability a person loses their ability to perform motor functions or in other words partial or complete paralysis, every human being today requires the help of a computer system which requires the ability of fingers. The target of this project is to create a interface which can help the disabled person interact with the operating system through their eyes, Here we are taking the help of the language python which provides us many libraries one of which is OpenCV, which provides us the feature of face detection and eye tracking.